2020
DOI: 10.34172/joddd.2020.019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of surface roughness changes on orthodontic acrylic resin by all-in-one spray disinfectant solutions

Abstract: Background. The disinfection of orthodontic acrylic resins might change the physical and mechanicalproperties of these materials. We aimed to investigate the impact of four different commercially availabledisinfectants on the surface roughness of acrylic resins used for orthodontic appliances. Methods. Four disinfectant solutions (BirexSE, Opti-Cide3, COEfect MinuteSpray, and CaviCideSpray) were used to disinfect orthodontic acrylic resins using the spraying method. The resins weresubjected to repeated disin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The evaluation of roughness average (Ra) is a common approach to test the surface of dental materials and how the environment impacts their surface's properties [ 35 ]. An increased roughness is usually more prone to microorganisms colonization and biofilm formation [ 18 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of roughness average (Ra) is a common approach to test the surface of dental materials and how the environment impacts their surface's properties [ 35 ]. An increased roughness is usually more prone to microorganisms colonization and biofilm formation [ 18 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes to the surface of the acrylic resin are related to an increase in microbial colonization and caused by the action of chemical and mechanical agents used during oral hygiene. Studies have indicated surface roughness induced by chemical products used for disinfection, specially solutions containing alcohol (Bensel et al 2019;Jo et al 2019), quaternary ammonium compounds, acids and anionic surfactants (Hsu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Determining the ideal antimicrobial solution that can disinfect acrylic resin without any short-term or long-term effects on the surface roughness of the material is challenging (Hsu et al 2020). A variety of agents and specific protocols are currently recommended for the disinfection of acrylic resin, with considerable concern regarding impact of the composition of disinfectant solutions (Badaró et al 2017) on the properties of the materials (Papadopoulou et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Surface roughness of the samples was measured with a contact roughness tester (Surftest SJ-210, Mitutoyo, Japan) according to the ISO 12179:2021 standard at the baseline and at four measuring stages, each of 2,500 cycles of toothbrushing simulation with a total of 10,000 cycles. At each measurement, three subsequent surface roughness values (Ra) were obtained from the top surface of each sample using a diamond tip stylus with tip radius of 2 μm and 60°angle at measuring force of 0.75 mN, a speed of 0.5 mm s −1 and a cut off value of 0.8 mm [14,15]. The three values were averaged to obtain a single value.…”
Section: Surface Roughness Measurementmentioning
confidence: 99%